Barriers and facilitators for the sexual and reproductive health and rights of displaced Venezuelan adolescent girls in Brazil - Leidy Janeth Erazo Chavez; Zeni Carvalho Lamy; Larissa da Costa Veloso; Laura Froes Nunes da Silva; Ana Maria Ramos Goulart; Natalia Cintra; Sarah Neal; Pía Riggirozzi (Journal of Migration and Health)
Background: The crisis in Venezuela has forced almost eight million people to flee to mainly neighbouring countries, including Brazil. Half of the displaced Venezuelans are women and girls, with adolescent girls facing distinctive challenges to their sexual and reproductive health during displacement and settlement. The aim of this study is to understand the barriers and facilitators for the sexual and reproductive health of adolescent Venezuelan girls residing in Brazil. Methods: The study used qualitative methods, including semi-structured interviews with 19 Venezuelan migrant adolescent girls conducted in Boa Vista and Manaus. We analysed transcripts using thematic analysis, and mapped findings to a theoretical framework based on the Bronfenbrenner Socio-ecological Model, which we adapted to explore how intersectional vulnerabilities at the individual level interact with contextual factors creating barriers and facilitators for health and rights of migrant adolescent girls. Results: Venezuelan adolescent migrants in Brazil face practical and structural barriers in realising their sexual and reproductive health and rights in four areas: menstruation; family planning, contraception and sexually transmitted infection; prenatal, childbirth and postnatal care; and preventing gender-based violence. The reported barriers were lack of knowledge around sexual and reproductive health rights, exposure to violence and lack of access to age-appropriate healthcare services. Mitigating factors included education (both in the family setting and at school); prevention activities undertaken by health services; care provision from non-governmental organisations and international agencies; and best practices in local health services. Conclusions: Host states must take action to enhance the right to sexual and reproductive health for adolescent migrants to allow them to make autonomous, independent and informed choices. A socioecological perspective on sexual and reproductive health and rights can help formulate intersectional policies that interconnect different levels of adolescent migrants’ experience.